2009
DOI: 10.1111/j.1365-2249.2009.03878.x
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii inhibits lipopolysaccharide-induced activation of human dendritic cells and T cell proliferation

Abstract: SummarySaccharomyces boulardii (Sb) is a probiotic yeast preparation that has demonstrated efficacy in inflammatory and infectious disorders of the gastrointestinal tract in controlled clinical trials. Although patients clearly benefit from treatment with Sb, little is known on how Sb unfolds its anti-inflammatory properties in humans. Dendritic cells (DC) balance tolerance and immunity and are involved critically in the control of T cell activation. Thus, they are believed to have a pivotal role in the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…In addition, we found the S. boulardii reference strain capable of inducing co-stimulatory functions and modulating chemokine receptor expression towards an activated DC phenotype primed for lymph node migration and efficient antigen presentation. These findings are supported by reports of S. boulardii modulating LPS induced CD80 and CCR7 expression [23], [35], and echo reports of commensal bacterial strains inducing DC maturation, as indicated by increased surface expression of CD80, CD86, and CCR7 [8], [10]. Our observation that yeasts belonging to the Saccharomyces genus are among the strongest cytokine inducing yeasts included in the present study, and that all included Saccharomyces yeasts induce DC cytokine profiles very similar to that induced by the S. boulardii reference strain, parallels the finding of a recent study where six live yeast strains representing the species S. bayanus , S. cerevisiae , and S. pastorianus induced non-discriminatory cytokine profiles in human PBMCs [24].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we found the S. boulardii reference strain capable of inducing co-stimulatory functions and modulating chemokine receptor expression towards an activated DC phenotype primed for lymph node migration and efficient antigen presentation. These findings are supported by reports of S. boulardii modulating LPS induced CD80 and CCR7 expression [23], [35], and echo reports of commensal bacterial strains inducing DC maturation, as indicated by increased surface expression of CD80, CD86, and CCR7 [8], [10]. Our observation that yeasts belonging to the Saccharomyces genus are among the strongest cytokine inducing yeasts included in the present study, and that all included Saccharomyces yeasts induce DC cytokine profiles very similar to that induced by the S. boulardii reference strain, parallels the finding of a recent study where six live yeast strains representing the species S. bayanus , S. cerevisiae , and S. pastorianus induced non-discriminatory cytokine profiles in human PBMCs [24].…”
Section: Discussionsupporting
confidence: 90%
“…The positive clinical effect of S. boulardii as seen in UC, CD and IBS could likely be dependent on factors other than a direct suppressive effect on DCs. A likely mechanism was shown by Thomas et al (2009), who showed that conditioned media from S. boulardii suppressed lipopolysaccharide-induced expression of DC activation, maturation markers CD40, CD80, and the migration receptor CCR7, and decreased the secretion of proinflammatory cytokines. Other studies have shown beneficial effects of S. boulardii in intestinal inflammation, involving the prevention of pathogen adherence to the intestinal cell wall, neutralization of bacterial endotoxins or improvements of the intestinal barrier (Pothoulakis et al, 1993;Tasteyre et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Three-or four-colour flow cytometric analysis (FACS) was used to identify and enumerate myeloid blood DC as described previously [14,20]. In some experiments mean fluorescence intensity (MFI) of fluorochrome-labelled cells was quantified using FACS.…”
Section: Facs Analysis Of MDCmentioning
confidence: 99%